Practical method in the diagnosis of diabetic ketoacidosis: end-tidal carbon dioxide - Kayalı, Ahmet; Bora, Ejder Saylav (The European Research Journal, 2024)
Objectives: Diabetic ketoacidosis (DKA) poses a life-threatening risk in uncontrolled diabetes. Current diagnostic criteria rely on invasive measures, leading to potential delays in treatment initiation. This study aimed to assess the diagnostic utility of noninvasive end-tidal carbon dioxide (EtCO2) measurements in DKA patients. Methods: A prospective, cross-sectional study was conducted in a tertiary-level Emergency Medicine Clinic from January 2021 to January 2023. Participants included adults with DKA symptoms and those with stable vital signs as controls. EtCO2 levels were measured using a capnograph device. Diagnostic criteria for DKA were blood glucose ≥250 mg/dL, ketonuria, ketonemia, and metabolic acidosis (pH